Fracture process analysis in Magnesia-Hercynite refractory materials by combining an enhanced Digital Image Correlation method with Wedge Splitting Test. (December 2021) - Khlifi, Imad; Pop, Octavian; Dupré, Jean-Christophe; Doumalin, Pascal; Huger, Marc
Highlights: The analysis of fracture process zone by coupling optical metrologies. The impact of energy dissipating mechanisms on fracture process zone. The impact of crack branching on the consumed energy. Abstract: Magnesia-Hercynite bricks destined for thermal shock applications in cement rotary kilns often show an enhanced crack propagation resistance due to an engineered microstructure design. In these materials, microcrack networks, resulting from the thermal expansion mismatch between magnesia matrix and Hercynite aggregates, promote the activation of energy dissipating mechanisms within the so-called Fracture Process Zone (FPZ) during loading. In this research, the fracture behaviour of a Magnesia-Hercynite material has been investigated by coupling an enhanced Digital Image Correlation method (2P-DIC) with the Wedge Splitting Test (WST). The coupling of these advanced characterisation methods is very effective in measuring important fracture parameters accurately and in highlighting characteristic fracture mechanisms, such as crack-branching. A refined R-curve approach is proposed with effective fracture energy calculations based on 2P-DIC measurements. The results demonstrate interesting correlations between FPZ development and an enhanced crack propagation resistance.